ZC4H2 deletions can cause severe phenotype in female carriers. Issue 5 (27th March 2017) - Zanzottera, Cristina; Milani, Donatella; Alfei, Enrico; Rizzo, Ambra; D'Arrigo, Stefano; Esposito, Susanna; Pantaleoni, Chiara
Abstract : ZC4H2 is involved in human brain development, and, if mutated, can be responsible for a rare X‐linked disorder, originally presented in literature as Wieacker–Wolff syndrome and Miles–Carpenter syndrome. In males, severe intellectual disability is associated with variable symptoms of central and peripheral nervous system involvement, such as spasticity, hyperreflexia, muscle weakness, and arthrogryposis. Female carriers are usually described as asymptomatic or only mildly affected. Here, we report on a girl carrying a de novo deletion of ZC4H2 detected by array‐CGH analysis. She showed a complex neurodevelopmental disorder resembling the clinical picture commonly observed in male patients. X‐inactivation was found to be random. Additionally, she had an unusual appearance of fingers and hand creases, and electromyography showed a peculiar pattern of both neurogenic and myopathic anomalies. The present patient confirms that female carriers can also be severely affected. Systematic clinical investigations of both males and females are needed to define the variety in nature and severity of phenotypes related to ZC4H2 variants.